Reliability of diagnosing acute ischemic cerebrovascular on magnetic resonance imaging disorders using iPads. - Hattori, Hidekazu; Kuwayama, Yoshifumi; Inui, Yoshitaka; Murayama, Kazuhiro; Hayakawa, Motoharu; Ito, Shinji; Toyama, Hiroshi (Japanese Journal of Radiology, 2018)
Purpose: The use of tablet terminals has been explored in various medical settings; however, caution should be exercised when performing image diagnosis using this technology. The present study examined the characteristics of an iPad Air™ monitor and assessed radiographic image interpretations to verify the reliability of the telediagnosis of acute cerebral infarction based on magnetic resonance imaging (MRI) using a tablet terminal.Materials and Methods: The luminance of the iPad Air™ was measured using a UA-10 analyzer, and radiographic image interpretation experiments were performed in 100 patients who underwent MRI within 6 h of symptom onset. Ten physicians viewed the images on the iPad Air™ and a medical monitor, with an interval of 2 months between each interpretation.Results: When the iPad Air™ screen was pure white, the contour lines revealed nonuniform luminance distribution. In the reading experiment, the areas under the curve of the medical monitor and the iPad Air™ were 0.9311 and 0.9431, respectively. No significant difference was observed between the medical monitor and the iPad Air™ (p = 0.113).Conclusion: The results of the observer performance studies for detecting acute ischemic cerebrovascular disorders on an iPad Air™ were found to be similar to those on a medical monitor.